Macroeconomic Fundamental Influence And Capital Structure against Company Values with Company Size as Variables Mediation in Healthcare Companies on the IDX 2021–2024 - Aminul Amin (CV. Ulil Albab Corp, 2026)
This study analyzes the influence of macroeconomic fundamentals and capital structure on firm value by considering the mediating role of firm size. The results show that GDP, as a proxy for macroeconomic fundamentals, has a positive and significant effect on firm value, reflecting that stable economic growth increases investor confidence and earnings prospects. Conversely, capital structure, as measured by DER, exhibits a negative and significant effect , indicating that high leverage lowers valuation due to the increased risk of financial distress and agency costs. More importantly, firm size serves as a significant mediating variable , strengthening the transmission path between external (macroeconomic) and internal (capital structure) factors on firm performance. These findings provide a theoretical contribution to understanding how external and internal factors interact through organizational dimensions. Practically, these results encourage management to design balanced strategic financial policies—for example, increasing capital structure efficiency while capitalizing on favorable macroeconomic conditions to optimize firm value in a dynamic economic environment.